Cult of analytics : driving online marketing strategies using Web analytics - Jackson, Steve; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier/Butterworth-Heinemann, 2009)
If you want to understand and get true value from your online content you need to understand how it is used by your customers. If you work with web analytics and online search optimization, this book will provide you with the tools and insight you need to do just that. Even more, it will give you an actionable plan to transform the culture of your organization into one that uses web analytics on a daily basis, focusing on real changes you can make to your department and processes to transform the way your business works. With examples from dozens of companies ranging from small businesses, to consumer sites like Amazon, to some of the largest companies in the world including Tesco and Google, Cult of Analytics demonstrates just how to apply web analytics to your business. * Unique: demand from marketers for a guide to building web analytics into business * Real-world examples show what does and doesn't work online to meet online business objectives * Covers both the technicalities of web analytics and the strategy behind using them in one handy guide to give marketers the complete picture.
The Organizational Hub and Spoke Method; Understanding Reach, Engage, Activate and Nurture (REAN); How to develop KPIs; Quick Wins and How to Use Them; The Tools of the Trade; Developing and Measuring Motivational and Behavioral Personae; Using the Insight Model to Improve Conversion and Retention; Simplified Reporting; The Proliferation Process.
Includes index.
Print version record.
Elsevier
Keywords: Internet marketing; Web usage mining; BUSINESS & ECONOMICS -- Marketing -- Telemarketing; BUSINESS & ECONOMICS -- Marketing -- Multilevel; BUSINESS & ECONOMICS -- Mail Order; BUSINESS & ECONOMICS -- Marketing -- Direct; BUSINESS & ECONOMICS -- E-Commerce -- Internet Marketing; Internet marketing; Web usage mining; Electronic books